2021
DOI: 10.1371/journal.pone.0257756
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals the molecular mechanism of yield increases in maize under stable soil water supply

Abstract: This study explored the physiological and molecular mechanisms of yield increase in maize under stable soil water content (SW) conditions. Results of the study showed that under SW conditions, corn yield increased by 38.72 and 44.09% in 2019 and 2020, respectively. Further, it was found that dry matter accumulation, economic coefficient and photosynthetic rate also increased by 31.24 and 25.67%, 5.45 and 15.38% as well as 29.60 and 31.83% in 2019 and 2020 respectively. However, the results showed that both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 23 publications
3
9
0
Order By: Relevance
“…Our enrichment analysis further showed that ATP synthesis and oxidative phosphorylation pathways were significantly enriched in SH19B, which provided clues to explore the molecular basis of the differences in response to heat stress among the three inbred lines ( Figure S3 ). Similar to our results, related transcriptome analyses have shown that oxidative phosphorylation plays an important role in response to environmental stress [ 38 , 39 , 40 ]. Mitochondria produce ATP through oxidative phosphorylation and also produce ROS, which causes damage to plant cells [ 41 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our enrichment analysis further showed that ATP synthesis and oxidative phosphorylation pathways were significantly enriched in SH19B, which provided clues to explore the molecular basis of the differences in response to heat stress among the three inbred lines ( Figure S3 ). Similar to our results, related transcriptome analyses have shown that oxidative phosphorylation plays an important role in response to environmental stress [ 38 , 39 , 40 ]. Mitochondria produce ATP through oxidative phosphorylation and also produce ROS, which causes damage to plant cells [ 41 ].…”
Section: Discussionsupporting
confidence: 91%
“…According to Wang (2020) , SW improved the photosynthesis of romaine lettuces and a similar phenomenon was observed in our findings. In addition, studies have found that under steady water supply, significant changes were observed in cell components linked to maize photosynthesis, including chloroplasts, plastids, and thylakoids, and genes such as psbE , psbF , psbA , and psbD related to photosystems were highly regulated ( Zhang et al., 2021b ). This may explain why SW increased the crop Photo.…”
Section: Discussionmentioning
confidence: 99%
“…This technology uses a water potential difference caused by the negative pressure system, soil evaporation and plant transpiration to control water supply, and it can continuously and stably supply water to plants, which helps manage soil water fluctuations ( Yang et al., 2022a ). The technology can not only be used for studying SWC effects on crop performance, but also for assessing the effects of soil water stability ( Zhang et al., 2021b ; Niu et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that irrigation at a greater depth in uenced cotton yield by inducing drought stress. Zhang et al [19] found that stable soil water content (SW) conditions not only increased maize (Zea mays L.) growth and yield signi cantly but also highly up-regulated expression of lots of DEGs in the photosynthesis (including PsbE, PsbF, PsbA, PsbD, etc.) and oxidative phosphorylation pathway (including atpE, atpB, ndhE, ndhG, etc.…”
Section: Introductionmentioning
confidence: 99%